The tribological properties of lubricating greases produced on vegetable base and modified of polytetrafluoroethylene - Kozdrach, Rafal (Tribologia - Finnish Journal of Tribology, 2020)
The article presents the results of research on the influence of polytetrafluoroethylene additive on the tribological and rheological properties of selected lubricant compositions. Based on the obtained test results, it was found that the introduction of a modifying additive to the lubricant structure allows a significant reduction of the coefficient of friction, thus increasing the efficiency of tribological protection of the tribosystem. All lubricating compositions modified with at least 1% polytetrafluoroethylene guarantee effective anti-wear protection under load conditions of the tribosystem. Modification of the tested lubricating compositions with the applied additive affects the increase of indicators characterizing the fatigue life of the examined lubricating greases based on sunflower oil. The introduction of the polytetrafluoroethylene into the structure of the tested lubricants changed the values of the MSD correlation function and the G’ and G’’ modules, which significantly influenced the internal structure of the tested lubricant compositions.